PENDAMPINGAN PEMBUATAN MESIN PENGGILING PADI OLEH KELOMPOK TANI LEMBUR AYU FARM DI DESA SEI MENCIRIM KECAMATAN KUTALIMBARU KABUPATEN DELI SERDANG - Salqaura, Siti Alhamra; Alfifto, Alfifto; Umroh, Bobby (Universitas Mataram, 2024)
Rice milling machines have a crucial role in the rice production process. Using rice milling machines can increase efficiency, productivity, and quality. This community service aims to increase knowledge related to the manufacture of rice milling machines to improve the productivity of community agricultural products. The method of community service is in the form of assistance in manufacturing rice milling machines with a total of 34 participants. The media used is a direct practice in the form of training and assistance. After the training and assistance activities, a post-test was conducted to measure the level of understanding of group members and the community. The results of this community service show that there is an increase in insight and understanding related to the manufacture of rice milling machines. Thus, it is hoped that the community will be able to operate the equipment and work sustainably, and be able to make rice milling machines in the future.